Programa de Ações Afirmativas da UFSCar: o processo de construção da política de reserva de vagas nos cursos de graduação - Pizza, Samira Nathalia (Universidade Federal de São Carlos, 2015)
This work is placed in the universe of affirmative action in higher education, emphasizing policies of vacancies reservation for black people in graduation courses. It was analyzed the development of the construction process of the Affirmative Action Program of the Federal University of São Carlos (UFSCar), between 2004 and 2007, being that the period before the implantation of the Affirmative Action Program from UFSCar, covering the stage of discussions and outlining a proposal for an affirmative action program for this university. This study aimed to discuss the vacancy reservation policy for black people in Brazilian higher education; verify the process that led on the introduction of vacancy reservation policy on the graduation courses of UFSCar and its consequences; analyze the process of elaboration and approval of the Affirmative Action Program from UFSCar, based on institutional documents and depositions of participants in this process. It is intended to understand what were the forces that acted for the approval of this policy at UFSCar and how this movement may have contributed on the national stage for the approval of Law n° 12.711.
Affirmative Action Program from UFSCar: the construction process of the vacancy reservation on graduation courses.
Keywords: Ações afirmativas; Reserva de vagas; Negros; Relações Étnico-raciais; Affirmative Action; Vacancy Reservation; Black People; CIENCIAS SOCIAIS APLICADAS::SERVICO SOCIAL